Diagnostic radiographers’ perspectives on dental radiography in selected provinces in South Africa - Keshini Govindasami; Shenuka Singh (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: Dental radiography forms part of the scope and training for a diagnostic radiographer in South Africa; yet there is limited published evidence related to these professionals’ knowledge, attitudes and practices on dental radiography.